UPAYA MENCEGAH STUNTING: PENYULUHAN TENTANG JANGAN HAMIL DI USIA DINI “JAMILUDIN” DI DESA KARANGREJO - Wahyu Nuralifah, Dina; Nabilah, Ihda; Daliya, Maysa; Maulidina, Rismayati; Islami, Wildah (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2024)
Abstract Stunting is a global problem that chronically hinders children's growth and development due to malnutrition and adequate nutrition. One factor that can contribute to stunting is early pregnancy. This study aims to explore efforts to prevent stunting through an outreach approach on the impact of early pregnancy in Karangrejo Village. Counseling is considered an effective instrument in increasing awareness and understanding of adolescents about the importance of taking blood-boosting tablets, the negative effects of pregnancy at an early age and its impact on child growth. This research method involves a qualitative approach by conducting interviews with Karangrejo Village officials on stuntinng and focus group discussions. The results revealed that stunting cases in the village were influenced by low understanding of stunting and the importance of nutrition during pregnancy. The counseling conducted succeeded in increasing the knowledge and awareness of the community and adolescents, describing the side effects of early pregnancy on child growth. In addition, this approach also mobilizes active community participation in overcoming this problem. This effort involves collaboration between health workers, village governments, and communities in providing the education and support needed. In conclusion, this study shows that counseling on the impact of early pregnancy can be an effective strategy in stunting prevention efforts in Karangrejo Village. By raising public awareness and knowledge and garnering cross-sectoral support, this approach has the potential to create significant change in tackling stunting and ensuring healthier growth of future generations. Keywords: Stunting, counseling, early pregnancy